VITA PRACTICA: ΦΡΟΝΗΣΙΣ AND ST. MAXIMUS THE CONFESSOR (Annual of the Faculty of Philosophy in Skopje, 2019)
As a continuation of Aristotle's definition of φρόνησις as a virtue by whichthe individual is competent in each individual case to find the optimal choice for actionthat in the background has the general picture of an eudaimonic life, in a specificmedieval context, φρόνησις is treated also in the philosophy of St. Maximus theConfessor. According to St. Maximus the Confessor, φρόνησις is an understandingof practical matters that are related to active life, namely “the deliberative power thatdetermines the right use of reason for those engaged in practice” (Amb Io. 1109B).In this text, the concept φρόνησις in the works of St. Maximus the Confessorthrough several aspects will be examined: creation as an expression of the Divineφρόνησις, φρόνησις within the systems of virtues and its function, φρόνησις asthe basis for vita practica and the relation between vita practica and vita contemplativa.Through these thematic points, the characteristics of φρόνησις in St. MaximusConfessor’s works will be drawn, which will show his aspirations for reconciliationof microcosmic antinomies with the macrocosmic paradigm of the eternal Logos.
Keywords: ST. MAXIMUS THE CONFESSOR; ФРОNHΣIΣ; VITA PRACTICA; VITA CONTEMPLATIVA